Transformation optics applied to van der Waals interactions - Zhao, Rongkuo (2016)
The van der Waals force originates from the electromagnetic interaction between quantum fluctuation-induced charges. It is a ubiquitous but subtle force which plays an important role and has a wide range of applications in surface related phenomena like adhesion, friction, and colloidal stability. Calculating the van der Waals force between closely spaced metallic nanoparticles is very challenging due to the strong concentration of electromagnetic fields at the nanometric gap. Especially, at such a small length scale, the macroscopic description of the dielectric properties no longer suffices. The diffuse nonlocal nature of the induced surface electrons which are smeared out near the boundary has to be considered. Here, we review the recent progress on using three-dimensional transformation optics to study the van der Waals forces between closely spaced nanostructures. Through mapping a seemingly asymmetric system to a more symmetric counterpart, transformation optics enables us to look into the behavior of van der Waals forces at extreme length scales, where the effect of nonlocality is found to dramatically weaken the van der Waals interactions.